Omni-directional Movement on the MRT PURVI Ship Robot - Wijaya, Ryan Satria; Kaputra, Aldi; Prasetyo, Naufal Abdurrahman; Soebhakti, Hendawan; Prayoga, Senanjung; Wibisana, Anugerah; Fatekha, Rifqi Amalya; Jamzuri, Eko Rudiawan; Nugroho, Mochamad Ari Bagus (Politeknik Negeri Batam, 2023)
Ship transportation is the primary mode of trade and transportation at sea in the maritime industry. Initially, humans employed ships as a method of pursuing and capturing fish or animals in aquatic environments. As the ship era progresses, it actively engages in all aspects pertaining to ships. Presently, the ship is propelled by its engine, which is a significant improvement over its initial reliance on wood or oars. In addition to engines, propellers are employed to transform the rotational motion of the engine into propulsive force in the marine environment. Propellers are also present on aircraft, serving the same purpose but positioned at various locations in the air. A thruster is a hybrid device that combines an engine and a propeller. This sort of thruster is specifically designed for use on tiny boats or prototypes, for the purpose of simulating, exhibiting, or participating in contests. ESC is a component that facilitates the alteration of the input value to the intended velocity. In addition to their primary function of fulfilling food requirements, ships are presently employed in diverse capacities, including military vessels, tourist vessels, submarines, passenger ships, and more.